Design and development of a versatile gripper - Ong, Jing Xiang (2016)
In this fast pacing world, grippers in the automation industries should be able to perform more tasks rather than a specific task like pick-and place. For a gripper to perform a specific task only, the productivity and efficiency will remain low. Therefore, many researches were done to implement dexterous manipulation or also called in-hand manipulation motions. With this additional feature, the gripper is able to perform more tasks and will be able to increase the productivity and efficiency in the factory. Despite many studies were done to implement in-hand manipulation motion in the gripper, most studies implemented one degree of freedom (DOF) in-hand manipulation motion only. Hence, the aim of this report is to design and develop a 2 DOF in-hand manipulation gripper. The gripper is able to manipulate an object weigh less than 500 grams in the rotation and sliding motion. A literature survey is conducted to identify the mechanisms used for the previous designs of in-hand manipulation grippers. After analyzing the mechanisms used and integrating new ideas, a 2DOF in-hand manipulation gripper is designed and fabricated. A four-bar linkage mechanism is used for the opening and closing movement of the gripper. Rotation motion is achieved by the actuation of a small DC motor whereas, the sliding motion is achieved by using a rack and pinion mechanism. From the test, it showed that the mechanisms applied in the gripper are able to work together simultaneously. Comparing with the grippers from other related researches, it showed that it is able to perform similar tasks in a shorter time and the lesser space is required as well. Since the gripper is still in the conceptual phase, there are still room for improvement to make the gripper better Further improvement and recommendation are included in the report.